2015
DOI: 10.1016/j.sbspro.2015.01.129
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Prevalence and Consequencies of Streets Begging among Adults and Children in Nigeria, Suleja Metropolis

Abstract: The study investigated the prevalence and consequences of street begging among adults and children in Suleja, Nigeria and its implication for counselling. Descriptive survey was adopted for the study, four research hypotheses were designed to guide the study. One hundred respondents were sampled from the four selected wards of the town. Data were collected through a well structured questionnaire by four experts in the field of the title. Chi-square (X 2 ) and Rank order statistical analysis were used as data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…Nigeria is one of many developing countries with a similar beggar-related issue to Indonesia. Bukoye (2015) confirms that the mushrooming of beggars has long been a social issue in Nigeria and has turned into the major drawback of global development. The same case is detected in Ghana and, according to Fuseini and Daniel (2018), the poverty of parents affects the number of child beggars in the country.…”
Section: Introductionmentioning
confidence: 75%
“…Nigeria is one of many developing countries with a similar beggar-related issue to Indonesia. Bukoye (2015) confirms that the mushrooming of beggars has long been a social issue in Nigeria and has turned into the major drawback of global development. The same case is detected in Ghana and, according to Fuseini and Daniel (2018), the poverty of parents affects the number of child beggars in the country.…”
Section: Introductionmentioning
confidence: 75%
“…Other coping strategies including starving to feed the children, sending the children to beg for food or money and sending children to stay in a relative's or friend's house were also employed by the households. Sending children to beg for food/money is not a common practice in the southern part of the country as opposed to the North, where children make up majority of street beggars [32]. Food insecurity is a real situation in the study area which must be tackled accordingly.…”
Section: Coping Strategies Of Respondentsmentioning
confidence: 99%
“…Many factors are considered as potential factors in enhancing the social evil of global child begging or begging at all, but the major factors are religion and poverty because it influences human behaviour (Zoumanigui, 2016). Bukoye reported that, when parents send their children for education away from home, then these children are sometimes forcefully incorporated into begging, some say that begging has taken the form of an industry now (Bukoye, 2015). Similarly, Magashi pointed out that among all the contributing factors of begging, poverty seems to be the most common and vibrant factor (Magashi, 2015).…”
Section: Introductionmentioning
confidence: 99%